Gender categorization between Islam and science: the problem of integration from Islamic jurisprudence perspective - Haneef, Sayed Sikandar Shah; Zahir, Ali Ahmed (Research Management Centre, International Islamic University Malaysia, 2016)
Modern science anatomically categorizes human babies at birth into four categories: male, female, true hermaphrodite and pseudo hermaphrodite. This binary juridical classification of humans into male (dhakar) and female (untha) concords mainly with the conclusions of science. Nevertheless, hermaphrodite`s (khuntha) configuration in Islamic jurisprudence presents a problem where some discordance can be observed between science and Islamic law. Likewise, traditional approach in Islamic law in managing hermaphrodites is challenged by their medical management. Therefore, this paper, while comparing the categorization of hermaphrodites from fiqh and scientific perspectives, points to the importance of fiqh procedures in managing hermaphrodites medically.